Dynamic properties of transducers testing using white noise excitation. Part 1: time domain - Hanus, Robert (Видавництво Національного університету “Львівська політехніка”, 2006)
This article deals with experimental non-parametric methods of parameters qualifying dynamic properties of transducers of voltage/voltage type using external stochastic input function (white noise) and cross-correlation function.